EU Capital Markets Union: the good, the bad and the ugly. (3rd July 2015) - Dorn, Nicholas
Abstract : This article broadly contextualises Capital Markets Union (CMU) in the Europe Union and introduces the three substantive articles that make up this symposium. The articles contain much substantive information, not only on the European Commission's public consultation in 2015 but also on trade responses to the consultation. Besides that, Kern Alexander, Ismail Ertürk and Dieter Pesendorfer offer some contrasting perspectives on CMU, suggesting respectively that it is along the right lines; that it needs better calibrating to the EU; and that it misses the opportunity to transform finance. The European Commission's further proposals, including legislation, flow from late 2015 onwards.